Pemanfaatan Sampah Organik Sebagai Briket:: Pemberdayaan Masyarakat Desa Sungai Landas - Tien Zubaidah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Suboptimal organic waste management often becomes a source of environmental pollution and health risks. In an effort to address this issue, lecturers from Poltekkes Kemenkes Banjarmasin implemented a community service program focusing on Clean and Healthy Lifestyle (PHBS) education and training on converting organic waste into economically valuable briquettes. The methods used included socialization, education about the negative impacts of waste burning, and training on briquette production using simple molding tools. Assistance and marketing guidance were also provided to support activity sustainability. This program involved the Sungai Landas Village community and community groups at the Cahaya Kencana landfill. Results showed significant improvement in community knowledge about organic waste management (from 45% to 85%) and waste sorting abilities (from 35% to 80%). Positive impacts were also observed in the community's commitment to implementing PHBS, which increased from 40% to 75%. Recommendations from this activity include the need for continuous support from the village government to provide small-scale waste management facilities, advanced training to expand community skills, and the formation of joint business groups to increase production capacity and briquette marketing. This program has the potential to be replicated in other villages to enhance economic independence and environmental quality sustainably.